Do rates of mental health symptoms in currently competing elite athletes in paralympic sports differ from non-para-athletes? - Olive, L. S.; Rice, S.; Butterworth, M.; Clements, M.; Purcell, R. (Sports Medicine - Open, 2021)
Background This study addresses the lack of comparative data on the mental health of athletes in Paralympic sports (`para-athletes`) and non-para athletes by examining the prevalence and correlates of mental health symptoms in a national sample of elite athletes representative of the population from which it was drawn on age and para-status.